The Teaching/Research Trade-Off in Law: Data From the Right Tail - Ginsburg, Tom; Miles, Thomas J. (Evaluation review, 2015)
Background: There is a long scholarly debate on the trade-off between research and teaching in various fields, but relatively little study of the phenomenon in law. This analysis examines the relationship between the two core academic activities at one particular school, the University of Chicago Law School, which is considered one of the most productive in legal academia. Method: We measure of scholarly productivity with the total number of publications by each professor for each year, and we approximate performance in teaching with course loads and average scores in student evaluations for each course. In OLS regressions, we estimate scholarly output as a function of teaching loads, faculty characteristics, and other controls. We also estimate teaching evaluation scores as a function of scholarly productivity, fixed effects for years and course subject, and faculty characteristics. Result: Net of other factors, we find that, under some specifications, research and teaching are positively correlated. In particular, we find that students’ perceptions of teaching quality rises, but at a decreasing rate, with the total amount of scholarship. We also find that certain personal characteristics correlate with productivity. Conclusion: The recent debate on the mission of American law schools has hinged on the assumption that a trade-off exists between teaching and research, and this article’s analysis, although limited in various ways, casts some doubt on that assumption.